Preparation and thermal properties of mineral-supported polyethylene glycol as form-stable composite phase change materials (CPCMs) used in asphalt pavements. Issue 1 (December 2017) - Jin, Jiao; Lin, Feipeng; Liu, Ruohua; Xiao, Ting; Zheng, Jianlong; Qian, Guoping; Liu, Hongfu; Wen, Pihua
Abstract Three kinds of mineral-supported polyethylene glycol (PEG) as form-stable composite phase change materials (CPCMs) were prepared to choose the most suitable CPCMs in asphalt pavements for the problems of asphalt pavements rutting diseases and urban heat islands. The microstructure and chemical structure of CPCMs were characterized by SEM, FT-IR and XRD. Thermal properties of the CPCMs were determined by TG and DSC. The maximum PEG absorption of diatomite (DI), expanded perlite (EP) and expanded vermiculite (EVM) could reach 72%, 67% and 73.6%, respectively. The melting temperatures and latent heat of CPCMs are in the range of 52–55 °C and 100–115 J/g, respectively. The results show that PEG/EP has the best thermal and chemical stability after 100 times of heating-cooling process. Moreover, crystallization fraction results show that PEG/EP has slightly higher latent heats than that of PEG/DI and PEG/EVM. Temperature-adjusting asphalt mixture was prepared by substituting the fine aggregates with PEG/EP CPCMs. The upper surface maximum temperature difference of temperature-adjusting asphalt mixture reaches about 7.0 °C in laboratory, and the surface peak temperature reduces up to 4.3 °C in the field experiment during a typical summer day, indicating a great potential application for regulating pavement temperature field and alleviating the urban heat islands.